P02.08 Visualizing tumor cell - lymphocyte interactions in the brain metastatic cascade using in vivo two photon microscopy - Piechutta, M (Neuro Oncol, 2018)
BACKGROUND: Despite high frequency of brain metastases (BM) in patients with advanced tumor stages and the process that immunotherapy becomes the treatment of choice in these cases, the activity and mechanisms of the adaptive immune response in BM is poorly understood. Current knowledge on the immunological tumor microenvironment is gained from in vitro- and ex vivo experiments, such as flow cytometry and immunohistochemistry. However, these methods fail to recapitulate the dynamic influx of lymphocytes and their interaction with tumor cells in the complex tumor microenvironment. A better understanding of lymphocyte recruitment, trafficking and activation in vivo is urgently needed to improve immunotherapeutic approaches. MATERIAL AND METHODS: To characterize the adaptive immune response in BM at single cell resolution, we developed a unique model allowing us to monitor these processes in vivo over weeks using repetitive two photon intravital microscopy. Recipient mice with a chronic cranial window were introduced with fluorescent glycoprotein-100 (gp100) positive syngeneic melanoma cells via heart injection or stereotactic injection into the cortex. Next, these mice received adoptive cell transfer of tumor-specific, fluorescently labeled CD8+ T cells from pmel-1 donor mice. RESULTS: It was possible to establish the first long-term imaging method to study dynamic lymphocyte- tumor cell interactions in the event of BM in vivo on a single cell level. CD8+ T cells could be recognized not only by its fluorescence signal but also due to their size and typical lymphocytic movement. We observed tumor-specific T cells to cross the brain blood barrier within a couple of hours and reside at the site of tumor for several days. Notably, transferred T cells were found in the tumor margin and inside the tumor but not in healthy brain parenchyma. CONCLUSION: Taken together, this preclinical model provides insights into the underlying mechanisms driving the immuno-response in vivo at high resolution. Importantly, it enables to further investigate and improve immunotherapeutic approaches with respect to prevention and therapy of BM.